Health risk assessment of electronic cigarette use among adults in selected populations in the Klang Valley, Malaysia - Zulkifli, Aziemah (2019)
Introduction: Introduction: The use of electronic cigarette (EC) is a common phenomenon in Malaysia despite the lack of evidence on its potential health risks. Advertised as safer and trendy than conventional cigarette, EC has been linked with the increment prevalence of users among non-smoker population worldwide. Besides being treated as a potential harm reduction tool by the smokers, the device remain controversial in the public health context due to the presence of hazardous and carcinogenic chemicals found in the refill liquid (e-liquid) that can adversely affect the users’ health. Objective: The overall aim of this study was to estimate the noncarcinogenic health risks due to exposure to nicotine and propylene glycol (PG) and carcinogenic health risk due to exposure to the two most potent tobacco-specific nitrosamines (TSNAs) present in locally-manufactured e-liquids, the liquid used in the EC. Methodology: This study was divided into three sub-studies, namely i) survey on EC use ii) chemical analysis of locally-manufactured e-liquids, and iii) health risk assessment of use of EC. This study was conducted from February 2016 until April 2017 in the Klang Valley, Selangor, Malaysia. In Sub-study I, proportion of EC users among 226 tobacco users and data on EC usage pattern were determined via a crosssectional survey. A purposive sampling method was applied in recruiting respondents. Questionnaire distributions involved three kinds of dissemination methods which were university-based, company-based and online-based sampling approach. In Sub-study II, a total of 17 samples of the most-favored e-liquid samples which have been reported by EC users in the Sub-study I were purchased in the vape shops around the Klang Valley. The chemical analysis involved the determination of nicotine and PG contents using gas-chromatography and the contents of two selected TSNAs (N-nitrosonornicotine (NNN) and 4-(methylnitrosamino) -1-(3-pyridyl) -1-butanone (NNK) using liquid chromatography mass-spectrometry (LC-MS/MS). Non-carcinogenic and carcinogenic health risks were estimated in the Sub-study III based on data obtained earlier. Results: Out of 226 of tobacco users in the Klang Valley, the results showed that the proportion of EC users was 38% (n = 86). Most users (58%) preferred the modified device which is also known as MOD type of EC. The average duration of EC use was one year with a frequency of five days a week. The preferred concentration of nicotine in e-liquids was 6 mg/mL. The reported volume of e-liquid used a day was 2 mL constituting two refills. The average levels of nicotine and PG present in locally-manufactured e-liquids were found to be 3.26 ± 1.04 mg/mL (range: 1.80-5.15 mg/mL) and 484.10 ± 98.24 mg/mL (range: 316.68-715.71 mg/mL), respectively. Nicotine was detected in all eliquid samples declared as “nicotine-free”. NNK and NNN were detected in all e-liquid samples with an average content of 0.0858 ± 0.0569 µg/L (range: 0.0160-0.1958 µg/L) and 0.3832 ± 0.2884 µg/L (range: 0.0418-0.9798 µg/L). It was estimated that the exposure to selected compounds in locally-manufactured e-liquids may pose both noncarcinogenic and carcinogenic risks to users where 2 out 10,000 of EC users face the risk of cancer. Conclusion: Thus, this study provided evidence on the need for a more stringent health policy in considering EC as a tool for harm reduction tool among heavy smokers and there is the need for the implementation of regulation on manufacturing and sales to prevent initiation of tobacco use among non-smoking adults to support the vision of achieving the End Game of Tobacco use by 2045.